2021
DOI: 10.31557/apjcp.2021.22.12.4043
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of miR-145-5p, DANCR and NRAS Expression Levels on the Survival Rate of Colorectal Cancer Patients

Abstract: According to the results of the study 2017, the age-adjusted incidence of colorectal cancer in Iran between 1990 and 2017 increased about 3.63%. Statistics show that the incidence and mortality of colorectal cancer are increasing in low-and middle-income countries, while in developed countries it is stable or declining

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…Approximately 3–5% of patients with CRLM have mutations within the NRAS gene [ 17 ]. A recent case–control study revealed that high expression of NRAS can increase the risk of CRC death up to four times (HR = 4.12, p = 0.045) [ 43 ]. In addition, Rezaei et al found that KDR was expressed at significantly higher levels in CRC tissues than in adjacent noncancerous tissues [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 3–5% of patients with CRLM have mutations within the NRAS gene [ 17 ]. A recent case–control study revealed that high expression of NRAS can increase the risk of CRC death up to four times (HR = 4.12, p = 0.045) [ 43 ]. In addition, Rezaei et al found that KDR was expressed at significantly higher levels in CRC tissues than in adjacent noncancerous tissues [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, when comparing gene expression in primary CRC tissues and adjacent noncancerous tissues, no statistically significant difference between the mRNA level of KDR in non-metastatic patients was found, implicating KDR as an interesting molecule to study further in the specific context of metastasis. 0.045) [43]. In addition, Rezaei et al found that KDR was expressed at significantly higher levels in CRC tissues than in adjacent noncancerous tissues [13].…”
Section: Discussionmentioning
confidence: 99%